Ultra‐high Performance Liquid Chromatography with Photodiode Array and Chemiluminescence Detection for the Determination of Polyphenolic Antioxidants in Erigeron acris L. Extracts. Issue 5 (20th July 2016) - Malejko, Julita; Nalewajko‐Sieliwoniuk, Edyta; Szabuńko, Julia; Nazaruk, Jolanta
Abstract: Introduction: The quality of herbs is directly related to the presence of polyphenolic antioxidants. This is the first report on the quantification of individual polyphenolic constituents of Erigeron acris L. Objective: To develop a new method using ultra‐high performance liquid chromatography with photodiode array and chemiluminescence (UHPLC‐PDA‐CL) detection for the separation and determination of polyphenols in Erigeron acris extracts. Methodology: The methanolic extracts from leaves and inflorescences of Erigeron acris were prepared by ultrasound assisted extraction. The chromatographic separation was performed on C18 column packed with 1.7‐μm particles. The post‐column CL detection was based on the enhancing effect of polyphenols on the CL generated in manganese(IV)–hexametaphosphate–formaldehyde system. Results: The UHPLC method allowed to separate polyphenols in a short running time (13 min), which was three times shorter compared with traditional HPLC. The CL detection was characterised by 6–48 times higher sensitivity and up to three times lower detection limits compared to PDA detection. Qualitative and quantitative differences were observed in polyphenolic composition of Erigeron acris extracts. The main components of leaves were scutellarin and chlorogenic acid, whereas in inflorescences quercetin 3‐ O ‐glucoside was predominant. Conclusion: Coupling of UHPLC with CL detection has been developed for the first time. This advanced chromatographic technique coupled with sensitive CL detection is a powerful approach for the investigation of polyphenolic profiles in natural products. The shorter analysis time and diminished waste generation makes the UHPLC method more environmentally friendly and more cost‐effective in comparison with conventional HPLC. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A new UHPLC‐PDA‐CL method for the determination of polyphenols in Erigeron acris L. extracts was developed. The method allowed to separate polyphenols in a short running time (13 min), which was three times shorter compared with traditional HPLC. The Mn(IV)‐based CL detection was characterised by 6–48 times higher sensitivity and up to three times lower detection limits compared to PDA detection. The main components of leaves were scutellarin and chlorogenic acid, whereas in inflorescences quercetin 3‐ O ‐glucoside was predominant.